Highly Efficient and Selective Gold Recovery Based on Hypercross-Linking and Polyamine-Functionalized Porous Organic Polymers - Ding, Rui; Chen, Yanli; Li, Yanhong; Zhu, Yancheng; Song, Cheng; Zhang, Xiaomei (ACS applied materials & interfaces, 2022)
With the continuous increase of electronic products, there is an urgent need to effectively recover gold from e-waste and other secondary resources other than the original mine. Here, hypercross-linking and polyamine-functionalized porous organic polymers (Pc–POSS–POP) were designed and facially synthesized based on multiple azo-coupling polymerizations between 2,9,16,23-tetraaminophthalocyanine (H2Pc(NH2)4) and octa(aminophenyl)-t8-silsesquioxane (OAPS) for the first time. The reaction requires no metal as a catalyst, thereby benefiting the purification of the product and the industrial scalability. Pc–POSS–POPs possess a hypercross-linking structure, highly conjugated frameworks, nitrogen-rich active sites, and extensively visible and near-infrared light absorption, which was utilized as an absorbent to retrieve Au (III). The results demonstrated that Pc–POSS–POPs have a high adsorption capacity (862.07 mg g–1) and a rapid adsorption rate toward gold recycling. The maximum adsorption capacity could reach up to 1026.87 mg g–1 as in the case of light irradiation. Due to the strong N coordination sites and the electronic interaction between the −NH4 + groups of Pc–POSS–POPs and AuCl4 –, Pc–POSS–POPs also exhibited excellent selectivity toward gold over several coordinated metals [Cr (VI), Co (II), Cd (II), Ni (II), and Hg (II)]. These properties together with the good regenerative ability and superior recyclability demonstrated that Pc–POSS–POPs possess promising potential as hypercross-linking polymers for capturing and recycling of Au (III).